A COMPARATIVE CLINICAL STUDY ON THE EFFECT OF UDVARTANA AND TUMMY TRIMMER IN UDARA- LAMBANATVA W. S. R CENTRAL OBESITY - Akki, *Manjunath; Hakkandi, Suresh; Hussain, Abid (International Journal of Ayurveda and Pharma Research, 2019)
Now a day’s Obesity/ Sthoulya is a burning issue, but it is not being easy to burn it. Abdominal obesity also known as central obesity. With all kinds of foods becoming readily available at any times while humans are sedentary, intake of higher energy and less energy expenditure. Ayurveda describes Medopachaya as Sthoulya, it is a Santarpanajanya vyadhi said as one among Asthanindita purusha. According to the WHO, obesity is one of the most common, yet among the most neglected, public health problems in both developed and developing countries. Globally 1 in 6 adults is obese and nearly 2.8 million individuals die each year due to overweight or obesity. India is just behind US and China in this global hazard list of top 10 countries with highest number of obese people. The diuretic and purgatives drugs are also used to treat obesity, but the action is for shorter term and the patients again put on weight after cessation of treatment. In Ayurveda we offer several treatment measures to treat obesity. Here is an attempt made with safety management using principles of Panchakarma. 30 Patients were equally divided in 2 groups and treated Udvartana with Kolakulatthadi churna and Tummy trimmer by Sauna shaping belt, their comparative effects in central obesity. On the other hand corporate sectors are selling commercial slimming belts and are being sold out like hotcakes. Comparing both the procedures, Udvartana has given better result than Tummy trimmer.